Debt consolidation with long-term debt - Alexander Scheer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The Great Recession has sent debt levels to a post-WWII high for several advanced economies, reviving the discussion of fiscal consolidation. This paper assesses the macroeconomic implications of tax-based versus spending-based consolidation within the framework of a New Keynesian model with long term government debt. Three results stand out: First, tax-based consolidations are inflationary whereas spending-based ones are deflationary. Second, the net benefits of inflation increase in the average maturity of outstanding debt: inflation revalues debt more efficiently, while distortions due to price dispersion remain unaffected - the maturity effect. Third, as a result, tax-based consolidations can become superior to spending cuts if the average maturity is high enough. Quantitatively, the threshold is two years for US data in 2013. The previous mechanism illustrates the importance of inflation in the consolidation process, even if raising its target rate is considered not to be an option.
Keywords: H63; E62; E31; 330